Factors Affecting Hotel Employee Performance in Indonesia During and After the COVID-19 Pandemic - Gaet Priyanto; Sujoko Sujoko (PT. Hafasy Dwi Nawasena, 2026)
The hospitality industry is a crucial sector in the Indonesian economy, heavily reliant on employee performance to maintain service quality and customer satisfaction. However, the COVID-19 pandemic has brought significant changes to work systems, organizational culture, and employee well-being. This study aims to identify factors influencing the performance of hotel employees in Indonesia during and after the pandemic through a systematic literature review of 18 articles published between 2020 and 2025. The results indicate that organizational culture, compensation, and the work environment have a positive effect on performance, while job stress has a negative impact, especially during the pandemic. Motivation, discipline, and work-life balance factors also strengthen the relationship between working conditions and performance. Overall, improving hotel employee performance requires an integrated approach that encompasses psychological, structural, and social factors in the work environment.